2019
DOI: 10.3389/fpsyg.2019.01752
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Classroom Social-Cognitive Processes in Bullying: A Short-Term Longitudinal Multilevel Study

Abstract: The aim of this study was to examine whether individual and classroom collective social-cognitive processes (moral disengagement and self-efficacy) were associated with bullying perpetration among schoolchildren. An additional aim was to examine whether changes in these processes from grade 4 (Time 1) to grade 5 (Time 2) were associated with a change in bullying perpetration. Self-reported survey data were collected from 1,250 Swedish students from 98 classrooms. Results of multilevel analysis indicated that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 69 publications
(119 reference statements)
5
40
1
Order By: Relevance
“…Taken together, our findings suggest that perceived efficacy to stop peer victimization, both at the individual level and at the classroom level, contribute to explaining variability in students' defending and passive bystanding. Although our results did not discern what caused what, previous research suggests that collective efficacy beliefs influence students' behavior, including peer aggression (Barchia & Bussey, 2011a; Thornberg et al, 2019; Williams & Guerra, 2011) and bystander behavior (Barchia & Bussey, 2011b). This is also in line with the social cognitive theory, which posits that human agency operates through a triadic codetermination process of causation (Bandura, 1986).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Taken together, our findings suggest that perceived efficacy to stop peer victimization, both at the individual level and at the classroom level, contribute to explaining variability in students' defending and passive bystanding. Although our results did not discern what caused what, previous research suggests that collective efficacy beliefs influence students' behavior, including peer aggression (Barchia & Bussey, 2011a; Thornberg et al, 2019; Williams & Guerra, 2011) and bystander behavior (Barchia & Bussey, 2011b). This is also in line with the social cognitive theory, which posits that human agency operates through a triadic codetermination process of causation (Bandura, 1986).…”
Section: Discussioncontrasting
confidence: 99%
“…Students might refrain from defending even if they have strong defender self‐efficacy beliefs, especially those having a low social status (Pöyhönen et al, 2010), as it could result in an increased risk of becoming future targets of peer victimization (Gini et al, 2008; Huitsing et al, 2014). Promoting and maintaining a high level of collective efficacy to stop peer victimization could foster the development of a positive and supporting classroom atmosphere (Thornberg et al, 2019), in which students are encouraged to stand up for victims of peer victimization. For example, collective efficacy could be nurtured by teaching different helping behavior and training both students and teachers in effective ways to deal with peer victimization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings on gender differences for passive bystanding have been mixed; some studies has found passive bystanding to be more common among girls (e.g., Salmivalli & Voeten, 2004), while others has found passive bystanding to be more common among boys (e.g., Pozzoli & Gini, 2012). A few studies also suggest that defending is negatively related to the number of students in the classroom (Peets et al, 2015;; but see null result in Thornberg, Wänström, Hong, & Espelage, 2017), and that pro-aggression is positively related to the proportion of boys in the classroom (Pozzoli et al, 2012b;Thornberg, Wänström, & Jungert, 2018).…”
Section: Control Variablesmentioning
confidence: 99%